Wallpapering sheet lining with nickel-chromium-molybdenum alloys guidelines. (Nickel Development Institute reference book series ;, 2000)
This document provides guidelines for the procedures employed in wallpapering carbon steel or alloy substrates with high nickel alloys such as UNS N10276 (Alloy C-276). The practices also are applicable to a wide range of lower alloyed nickel-containing materials where appropriate.